2010
DOI: 10.1038/ng.630
|View full text |Cite
|
Sign up to set email alerts
|

Haploinsufficiency for the erythroid transcription factor KLF1 causes hereditary persistence of fetal hemoglobin

Abstract: Hereditary Persistence of Fetal Hemoglobin (HPFH) is characterized by persistent high levels of fetal hemoglobin (HbF) in adults. Several contributory factors, both genetic and environmental, have been identified 1, but others remain elusive. Ten of twenty-seven members from a Maltese family presented with HPFH. A genome-wide SNP scan followed by linkage analysis revealed a candidate region on chromosome 19p13.12–13. Sequencing identified a nonsense mutation in the KLF1 gene, p.K288X, ablating the DNA binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
367
5
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 348 publications
(398 citation statements)
references
References 36 publications
18
367
5
8
Order By: Relevance
“…KLF1 (or EKLF) is a critical erythroid regulator required for adult β-globin transcription (11). Recently it was shown that KLF1 occupies the BCL11A promoter and activates its expression (12,13). Consistent with previous analysis, knockdown of BCL11A or KLF1 results in marked increase in γ-globin expression and serves as positive controls for the RNAi screen.…”
Section: Bcl11a-interacting Partner Proteins In Erythroid Cellssupporting
confidence: 68%
“…KLF1 (or EKLF) is a critical erythroid regulator required for adult β-globin transcription (11). Recently it was shown that KLF1 occupies the BCL11A promoter and activates its expression (12,13). Consistent with previous analysis, knockdown of BCL11A or KLF1 results in marked increase in γ-globin expression and serves as positive controls for the RNAi screen.…”
Section: Bcl11a-interacting Partner Proteins In Erythroid Cellssupporting
confidence: 68%
“…49 In humans, haploinsufficiency for KLF1 causes hereditary persistence of fetal hemoglobin. 50 In erythrocyte progenitor cells, KLF1 was upregulated 28-fold when compared with hematopoietic stem cells. 22 ALDH8A1 converts 9-cis-retinaldehyde into the 9-cis-retinoic acid, which influences hematopoiesis in the fetal liver.…”
Section: Genetic Loci Influencing Red Blood Cell Traitsmentioning
confidence: 99%
“…The BCL11A locus is represented by SNP rs11886868, where the high-HbF (and protective) allele is 'C' in all populations studied so far (22,(25)(26)(27). In the Colombian samples, the two alleles have a nearly equal frequency (T=0.492 and C=0.508) (table 2).…”
Section: Resultsmentioning
confidence: 99%